ANALISIS TINGKAT KESEHATAN BANK MENGGUNAKAN METODE PROFIL RISIKO, TATA KELOLA PERUSAHAAN YANG BAIK, PENDAPATAN & MODAL (Studi Komparasi Antara Bank Umum Konvensional dan Bank Umum Syariah Di Indonesia Lemabaga yang Terdaftar Pada Otoritas Layanan Keuangan - Gusganda Suria Manda; Rina Maria Hendriyani (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2020)
This analysis aims to find out, analyze and explain how the bank's soundness level compares with the Risk Profile, Good Corporate Governance, Earning and Capital methods in accordance with applicable regulations. This research was conducted using a comparative descriptive method with a quantitative approach. The results of the analysis of this study the authors get that Conventional Commercial Banks have a Risk Profile (NPL ratio) with a rating of